Students lived experiences with technology in mathematics learning: a hermeneutic phenomenological study in Indonesian secondary education - Anisa, Siti; Ginashantika, Evana; Sudirman, Sudirman; Olivero-Acuña, Ronaldo Rafael (Nashir Al-Kutub Indonesia, 2025)
This hermeneutic phenomenological study explores the lived experiences of ten Grade XI students in a private secondary school in West Lombok, Indonesia, regarding technology use in mathematics learning. Through open-ended and closed questionnaires analyzed using Braun and Clarke's six-phase thematic analysis, four primary themes emerged: understanding mathematics, motivation and learning interest, impact on learning outcomes, and learning accessibility. Findings reveal that technology plays a paradoxical role in mathematics education, simultaneously enhancing conceptual understanding through interactive visualizations while being unable to fully replace adaptive teacher explanations. Students reported increased engagement and improved academic performance, yet also experienced challenges including digital distractions and decreased intrinsic motivation. Accessibility benefits were offset by persistent digital equity issues affecting students with limited technological resources. These findings support a complementary integration approach where technology enhances rather than replaces traditional pedagogical methods. The study contributes nuanced insights into how Indonesian secondary students interpret and experience technology-mediated mathematics learning, providing empirical evidence for educators and policymakers to design more effective, equitable, and meaningful technology integration strategies in mathematics education.